ENTRE IMIGRANTES E NATIVOS DIGITAIS: USOS E RELAÇÕES COM O COMPUTADOR - Silva, Fabiana Cabrera (2010)
Considering the relevance of the subject in the discussions of education and new technologies in the contemporary society, the present research of exploratório matrix, it considers to understand relation of the adults and children with the computer and as it measured (or not) is relation. Taking the parents and the educator as immigrant and the digital children as native of the group of 1º Year of EF I, a private school education, in São Bernardo do Campo. It is a quantitative research in the measure where it studies the frequency with that the data appear between the group of participants and qualitative a time that appeals to the strategies of collection of data such as: wheel of colloquy with the students; questionnaire, e-mails and group of quarrel with the parents (father or mother); questionnaire, e-mails and interviews with the teacher. And as the theoretical results of this work for authors such as: BABIN & KOULOUMDJIAN (1989); KEYS & SETZER (1980); HUIZINGA (2001); LÈVY (1993; 1996; 1999); KENSKY (2003; 2007); MORAN (1987; 2007); PAPERT (2008); BRAVE (2002); SANCHO (1998); QUEIROZ (1999), SÁ (2001) that they had contributed in the measure where they make possible a conversation between its ideas, conceptions and with the voices of the participants of the research. The results go to understanding what the computer for the students is related to the relation between: infancy, experience, playfulness as elements for the construction of the knowledge; for the parents a possibility still in adaptation, but that it requires orientation; e for the teacher still the technology seems still to be in the limits of the field of the resistance, probably in result of the incongruity between qualification and politics of teaching work. The work leaves questions, expecting to stimulate, with this, new studies